Some Ethnophytomedical Aspects and Conservation Strategy of Several Medicinal Plants in Java, Indonesia - HARINI M. SANGAT; INGE LARASHATI (Biodiversitas Journal of Biological Diversity, 2002)
The importance of medicinal plants for the preparation of â€œjamu" has been recognized in Indonesia and especially Java since ancient times. Jamu usually consists of blends of several kinds of plants or other natural materials. Jamu remains popular and there is an increasing demand for jamu in such diverse fields as health and beauty care, medical treatment and the preparation of fresh beverages. The problems result from the fact of most materials needed for preparation of jamu being natural resources. These materials are collected by the people in the forest and sold to the producers without thought for the conservation of these plants in nature with the consequence that some of the medicinal plants concerned have become difficult to find in the wild. Studies in the field in West, Central and East Java and at jamu enterprises and raw material sales centre show that several species of jamu raw material are very scarce. They should be classified as endangered. In this paper the significance of the endangered species as jamu in traditional Indonesian medicine is assessed and a strategy for conserving them "in situ and ex situ " is discussed.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: conservation, medicinal plant, jamu, Java.